Impact of Migration on the Utilization of Antenatal Care Services among Women of Urban Slums in Bangladesh (Dhaka University Journal of Science, 2022)
Mothers living in urban slums in Bangladesh get far less access to maternal and child health care services which may lead to mortality or serious morbidity to mothers as well as newborns. Lack of antennal care (ANC) is closely linked to poor pregnancy outcomes including low birth weight, preterm births or infant mortality. However, exposure to migration makes the situation worse in terms of attending urban community health care facilities among women in slums. Since the effect of migration on the usage of antenatal care services in slums has remained an under studied area, this paper aims to examine the adjusted effect of migration on perceiving adequate ANC. Data from the second round of Bangladesh Urban Health Survey conducted in 2013 have been used for this study. A well fitted binary logistic model resulted in lower odds of receiving complete ANC among recently migrated women in slums (AOR=0.602, 95% CI=0.43-0.85). Therefore, further emphasis should be given to increase awareness about antenatal care services among women who are recently migrated to urban slums in Bangladesh.Dhaka Univ. J. Sci. 70(2): 8-14, 2022 (July)